### 9 Answers

multiply the 2 parts by a :

5+3a = 3-2a

So

5a = -2

a=-2/5=-0.4

If you mean to ask your problem as written,

5 / a + 3 = 3 / a – 2 yields a = (-2 / 5).

If you meant the problem to be

5 / (a + 3) = 3 / (a – 2),

then be sure to use parentheses to show the proper order of operations when writing your problem on one line.

5 / (a + 3) = 3 / (a – 2) can be solved by cross-multiplying, like any proportion.

5(a – 2) = 3(a + 3) [Distribute.]

5a – 10 = 3a + 9 [Add (-3a + 10) to both sides to isolate the variable.]

2a = 19

a = 19 / 2 = 9 1/2 = 9.5

a= 9 1/2

If you meant: 5 / (a +3) = 3 / (a – 2), then do it like this.

Multiply both sides by [(a + 3)(a – 2)].

5(a – 2) = 3(a + 3)

5a – 10 = 3a + 9

2a = 19

a = 19/2 or 9.5

If you meant what you typed, which is 5/a + 3 = 3/a – 2, then do this.

Add 2 to both sides.

5/a + 5 = 3/a

Now, multiply everything by “a”.

5 + 5a = 3

5a = -2

a = -2/5 or -.4

2a=-5

Multiply both sides of the equation by to get rid of the denominator a. You then get the equation 5+3a=3-2a. Subtract 5 from both sides to get 3a-=-2-2a. Add 2a to both sides to get 5a=-2. solve for a by dividing both sides by 5. answer: a=-2/5

(5/(a + 3)) = (3/(a – 2))

cross multiply

5(a – 2) = 3(a + 3)

5a – 10 = 3a + 9

2a = 19

a = (19/2)

5/a+3=3/a-2

take same varibles on same side

5/a-3/a=-2-3=-5

2/a=-5

a=-(2/5)

5(a-2)=3(a+3)

2a=19

a=9.5